2022
DOI: 10.1002/emp2.12660
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric sepsis phenotypes for enhanced therapeutics: An application of clustering to electronic health records

Abstract: Objective The heterogeneity of pediatric sepsis patients suggests the potential benefits of clustering analytics to derive phenotypes with distinct host response patterns that may help guide personalized therapeutics. We evaluate the relative performance of latent class analysis (LCA) and K‐means, 2 commonly used clustering methods toward the derivation of clinically useful pediatric sepsis phenotypes. Methods Data were extracted from anonymized medical records of 6446 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…On the other hand, Phenotype 2 is characterized by low severity with only a few elevated WBC parameters, phenotype 3 shows moderate severity with mild tachypnea, and phenotype 4 presents high severity with liver dysfunction with hypoxia. These 4 phenotypes were found to match well with the phenotypes from the other data set, demonstrating moderate reproducibility ( 60 ).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…On the other hand, Phenotype 2 is characterized by low severity with only a few elevated WBC parameters, phenotype 3 shows moderate severity with mild tachypnea, and phenotype 4 presents high severity with liver dysfunction with hypoxia. These 4 phenotypes were found to match well with the phenotypes from the other data set, demonstrating moderate reproducibility ( 60 ).…”
Section: Introductionmentioning
confidence: 69%
“…For example, Koutroulis et al, 2022 and ( 61 , 62 ) estimated the smallest sample size to delineate phenotypes through simulation experiments. As a result, both found that 150 samples were enough to identify 4 distinct phenotypes with 80% power ( 60 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning potential methodological weaknesses of this study, it should be noted that, in a head-to-head comparison of LCA versus k-means clustering in a relatively small sample of pediatric patients with sepsis (n=151), LCA was found to be somewhat more useful in identifying homogeneous phenotypes. However, both approaches identified at least one distinct high-severity phenotype [ 96 ]. Given that LCA is computationally challenging whereas k-means is better scaled to large data sets [ 97 ], most critical medicine clustering studies involving large cohorts (N>1000) in sepsis [ 20 ], ARDS [ 98 ], and COVID-19 [ 99 , 100 ] have effectively used k-means to identify well-separated phenotypes, leading to early detection of those who would benefit from certain treatments and close monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…ML algorithms, in addition to detecting occurrences of a particular phenotype, can also enrich current phenotypes by expanding them into levels of severity or subtypes. As examples, two recent papers used latent class analysis to identify sub-phenotypes of acute respiratory distress syndrome [121] and pediatric sepsis [122]. Elucidating phenotype stratification is important as different sub-phenotypes often require different treatment strategies and responses.…”
Section: Machine Learning and Artificial Intelligencementioning
confidence: 99%